Submaximal, perceptually regulated exercise testing predicts maximal oxygen uptake: A meta-analysis study - Coquart, J.; Tabben, M.; Farooq, A.; Tourny, C.; Eston, R. (Sports Medicine, 2016)
Recently, several authors have proposed the use of a submaximal `perceptually regulated exercise test` (PRET) to predict maximal oxygen uptake (VO2max). The PRET involves asking the individual to self-regulate a series of short bouts of exercise corresponding to pre-set ratings of perceived exertion (RPE). The individual linear relationship between RPE and oxygen uptake (RPE:VO2) is then extrapolated to the VO2max, which corresponds to the theoretical maximal RPE (RPE20). Studies suggest that prediction accuracy from this method may be better improved during a second PRET. Similarly, some authors have recommended an extrapolation to RPE19 rather than RPE20.